2023
DOI: 10.3390/plants12081716
|View full text |Cite
|
Sign up to set email alerts
|

Sideritis scardica Extracts Demonstrate Neuroprotective Activity against Aβ25–35 Toxicity

Abstract: Alzheimer’s disease (AD) is the most prevalent neurodegenerative condition, primarily affecting seniors. Despite the significant time and money spent over the past few decades, no therapy has been developed yet. In recent years, the research has focused on ameliorating the cytotoxic amyloid beta (Aβ) peptide aggregates and the increased elevated oxidative stress, two interconnected main AD hallmarks. Medicinal plants constitute a large pool for identifying bioactive compounds or mixtures with a therapeutic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…More specifically, natural products with antioxidant and neuroprotective properties against AD represent a highly developing field with the potential to offer valuable drugs or nutraceuticals [ 5 ]. Although various groups have revealed the neuroprotective properties, mainly of S. scardica extracts in cellular and animal models [ 23 , 25 , 26 , 28 , 30 ] as well as in humans [ 33 , 34 , 35 ], very scarce data exist on another Sideritis taxon, SCP, and its neuroprotective properties. Moreover, it is noteworthy that, so far, only Sideritis spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, natural products with antioxidant and neuroprotective properties against AD represent a highly developing field with the potential to offer valuable drugs or nutraceuticals [ 5 ]. Although various groups have revealed the neuroprotective properties, mainly of S. scardica extracts in cellular and animal models [ 23 , 25 , 26 , 28 , 30 ] as well as in humans [ 33 , 34 , 35 ], very scarce data exist on another Sideritis taxon, SCP, and its neuroprotective properties. Moreover, it is noteworthy that, so far, only Sideritis spp.…”
Section: Discussionmentioning
confidence: 99%
“…They were also shown to promote non-amyloidogenic amyloid precursor protein (APP) processing and to reduce total and hyperphosphorylated tau protein levels in cellular models for AD [ 25 ]. Similarly, various fractions of S. scardica extract demonstrated activity against Aβ toxicity, while antioxidant properties were revealed for almost all these fractions [ 26 ]. The mid-polar extracts of S. scardica conferred a reduction in Aβ aggregates in various AD Caenorhabditis elegans models, accompanied by a significantly delayed paralysis rate [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro and in vivo studies have shown that plant-derived extracts and their phytoconstituents can protect cells and tissues form oxidative damage through direct radical-scavenging mechanisms but also through indirect modulation of redox-sensitive pathways and the induction of cellular antioxidant responses [ 51 ]. Recent research indicates that S. scardica is rich in phenolics and flavonoids and can exert significant antioxidant activity [ 3 , 18 ]. Sideritis extracts have been shown to produce beneficial effects on characteristics of dementia and Alzheimer’s disease since they can inhibit the aggregation and toxicity of amyloid-β in vivo [ 13 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preparations of S. scardica are used for the treatment of chest illnesses, bronchitis, intestinal diseases, pulmonary emphysema, angina pectoris and urinary tract infections [ 9 ]. Additionally, the protection against oxidative damage is one of the most widely described attributes of polyphenols of S. scardica and is connected with their antioxidant activity [ 9 , 18 ]. In recent human clinical studies, S. scardica supplementation resulted in improved cognitive performance due to increased cerebral blood flow [ 19 ], while S. euboea extract supplementation was effective in lowering total cholesterol levels in adults [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most promising of these four extracts are SFDE and SFEA, which present similar anti-amyloid activity as the rest, but also an enormous antioxidant ability, which is relatively high in comparison to other medicinal plants [ 73 ]. Furthermore, their anti-amyloid capacity is similar to extracts from other medicinal plants that are considered neuroprotective, as well [ 74 , 75 , 76 ]. However, SFDE and SFEA do not completely restore the viability of the cells, as other individual compounds or specific extracts from other plants do [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%